Effect of the Lavender, sesame oil, combination of Lavender with sesame oil and silver sulfadiazine on the burn wound healing in mice - Aria Afshari; Mahdieh Raeeszadeh; Loghman Akradi (مجله دانشگاه علوم پزشکی گرگان, 2018)
Background and Objective: Burn is one of the leading causes of mortality in the world. This study was done to determine the effect of the lavender, sesame oil, and combination of Lavender with sesame oil and silver sulfadiazine on the burn wound healing in mice. Methods: In this experimental study, 30 male adult albino mice were randomly allocated into 5 groups as follows: the negative control group (physiology serum); the positive control group (silver sulfadiazine); the first experimental group (sesame oil), the second experimental group (combination of Lavender with sesame oil) and the third experimental group (Lavender oil).Second degree of  burn wound healing  take place using hot sheet with a diameter of 2 cm. wound treatment was done in five groups in 21-day treatment period. The wound diameter size and restoration percentage were measured on days 1, 3, 6, 9, 18, and 21. Some mice were euthanized and the samples of wounds were used for histopathological studies. Results: The percentage of wound healing significantly increased in groups of silver sulfadiazine, combination of Lavender with sesame oil, Lavender oil and  sesame oil in compared to control group (P<0.05). The improvement percentage was seen in sulfadiazine and combination of Lavender with sesame oil groups in compared to negative control group. The level of tissue restoration based on the accumulation of collagen, fibroblasts, re-epithelialization were seen in sulfadiazine, combination of Lavender with sesame oil, Lavender oil and sesame oil, respectively. Conclusion: Combination of Lavender with sesame oil similar to silver sulfadiazine has tissue restoration effect on burn wound healing in animal model.